The Leadership of Sultan Barquq and the Development of the Burji Mamluk Dynasty in Egypt (1382–1517 CE) - Mawaddah, Shofiyya; Aminudin, Muhammad; Firmansyah, Mochamad Azharuddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine the leadership of Sultan Barquq and the development of the Burji Mamluk Dynasty in Egypt (1382–1517 CE). The main focus of this research is to understand the aspects of leadership, dynastic development, and the challenges faced during that period. A qualitative historical method was used, with a library research approach involving journal articles, history books, and related documents.The findings show that during Sultan Barquq’s reign, he successfully seized power by overthrowing Sultan Hajji of the Bahri Mamluk Dynasty in 1382 CE and officially became sultan in 1389 CE. He consolidated his power by placing family members in key positions and strengthening the military. Under Sultan Barquq's leadership, the Burji Mamluk Dynasty experienced significant progress in maintaining Egypt’s stability against external threats, preserving its strategic position along regional trade routes, and strengthening its rule through political consolidation and military enhancement. The Burji Mamluks successfully repelled attacks from Timur Lenk’s forces, the Mongols, and Crusaders in the Mediterranean. However, the dynasty ultimately fell to the Ottoman Turks due to internal instability caused by frequent changes of sultans and conflicts among the amirs, which weakened the Burji Mamluk Dynasty.